Analysis of soil nitrate ion selective slectrode (ISE) sensor using Arduino UNO - Ashraffarhan, Awang Mohd; Mohd Salleh, Mohd Hazimin; Muhamad Tajudin, Nur Shuhada (Universiti Tun Hussein Onn Malaysia Publisher, 2022)
The ecological concern over soil and groundwater pollution caused by agricultural activities has led to the growing interest in precision agriculture. One of the most common types of fertilizer is the nitrogen fertilizer which needed in major amount for plant growth. Over fertilization will contaminate soil and groundwater which can have adverse effect on environment and human health. The main purpose of this research is to measure soil nitrate concentration using nitrate ion-selective electrode (ISE) sensor and Arduino programmable microcontroller. The optimum soil-to-water ratio and the effect of soil solution clarity will be investigated. Standard sampling procedures was conducted at oil palm plantation area, Felda Bukit Goh, Pahang, Malaysia. Validation of the results were carried out in the laboratory. The recorded data indicated accurate readings for Nitrate ISE Arduino was R² = 0.84. The soil to-water ratio of 1:2.5 was observed as an optimal proportion ISE analysis. A clear soil solution was crucial for maintaining the accuracy of ISE sensor, to avoid declining of 46.2% accuracy. These results could assist researchers and farmers to accurately monitor the concentrations of soil nitrate on the field effectively as well as an insight to ISE sensor with Arduino technologies.